Fundamentals of Biomechanics - Second Edition - Knudson, D. (Springer, 2007)
Fundamentals of Biomechanics, is an attempt to bridge the gap between quantitative and qualitative biomechanics. The book is remarkably well written, the structure is well designed and all the examples are carefully selected in order to enhance the understanding of the students. Additionally, the mechanical and biological concepts are exceptionally well integrated. This increases the spectrum of fields of application. The book should be read by students and professionals from all over the world. The reason is that Duane Knudson explains biomechanics for students, coaches, physiotherapists and medical doctors in comprehensive aspects of human movements clearly and simply with a biological and predominantly qualitative approach. (Krug)